Self-Learning Activity Package in Occupation Skills Development for Primary Education Students (Grade 6) Wat Samuha Rat Bamrung School - Dulklang, Thanyathorn; Sangsawang, Thosporn (Universitas Pendidikan Indonesia (UPI), 2021)
The purposes of this study were to: (1) find efficacy of self-learning activity package in occupation skills development for primary education students, (2) understand effectiveness of students’ learning skills before and after learning, and (3) know students’ satisfaction self-learning activity package in occupation skills development for primary education students towards self-learning activity package in professional skills development. The study tested 30 sixth-grade students in Career and technology education course during the first semester of 2020 at Wat Samuha Rat Bamrung School, Thailand. Research instruments comprised self-learning activity package in occupation skills development, completed with pre-test, post-test, and satisfaction survey. The findings indicated that self-directed learning activity package in professional skills development met the standard for effectiveness at 81.25/80.56. Students’ learning skills were significantly improved after training as evidenced by the mean and the standard deviation scores. Additionally, the result of the t-test analysis between pre-course and post-course was 4.80 with the statistically significant difference of 0.05 level. The level of students’ satisfaction on self-learning activity package in occupation skills development for primary education students appeared at the highest with the mean score of 4.90.